2006
DOI: 10.1243/09544100g05004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inlet swirl on the performance of annular diffusers having the same equivalent cone angle

Abstract: Annular diffusers are an integral component of the gas turbine engines of high-speed aircraft. These facilitate effective operation of the combustor by reducing the total pressure loss. The performance characteristics of these diffusers depend on their geometry and the inlet conditions. The present investigation attempts to select the range of the inlet swirl intensity for the best performance of annular diffusers with different geometries but having the same equivalent cone angle. This is analysed on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Senoo et al [8] and Okio et al [9] obtained similar results for conical diffusers using a Rankin-vortex inlet swirl distribution. Moreover, Kumar and Kumar [10], Singh et al [11], and Mohan et al [12] obtained similar findings for annular diffusers. For conical diffusers, Senoo et al [8] made the point that there exists an optimum diffuser opening angle with a corresponding optimum level of inlet swirl.…”
Section: Introductionsupporting
confidence: 54%
“…Senoo et al [8] and Okio et al [9] obtained similar results for conical diffusers using a Rankin-vortex inlet swirl distribution. Moreover, Kumar and Kumar [10], Singh et al [11], and Mohan et al [12] obtained similar findings for annular diffusers. For conical diffusers, Senoo et al [8] made the point that there exists an optimum diffuser opening angle with a corresponding optimum level of inlet swirl.…”
Section: Introductionsupporting
confidence: 54%
“…Singh et al [12]; Singh et al [13] showed the improvement in the performance of annular diffuser by using swirl flow in their experimental data. It is found that flow separation occurs on the hub wall and diminishes the performance beyond the swirl angle 30°.…”
Section: Introductionmentioning
confidence: 99%
“…Armfield and Fletcher [16] and Mahalakshmi et al [17] analyzed the conical diffuser using numerical method with Reynolds stress and k-e models and experimental method, respectively. Singh et al [18] have carried out CFD studies using FLUENT code in annular diffusers with different geometries but having same inlet cone angle.…”
Section: Introductionmentioning
confidence: 99%